The Influence of Quality, Facilities and Location on Tourists' Decisions to Visit Je'ne Tallasa Sileo Baths, Gowa Regency - Arqham, Darul; Jamaluddin, Jamaluddin; Niswaty, Risma (Pinisi Business Administration Review, 2026)
This research examines the influence of quality, facilities and location on tourists' decisions to visit Je'ne Tallasa Sileo Baths, Gowa Regency, partially and simultaneously. The aim of this research is to determine the influence of quality, facilities and location on tourists' decisions to visit Je'ne Tallasa Sileo Baths, Gowa Regency, partially and simultaneously. This research approach is quantitative. This research was carried out at the Je'ne Tallasa Sileo Baths, Gowa Regency. Respondents in the research were tourists at the Je'ne Tallasa Sileo Baths, Gowa Regency. Data collection techniques include observation, questionnaires and documentation. Data analysis techniques include validity tests, reliability tests, normality tests, multiple linear regression analysis, and determinant coefficient analysis. The results of the research show the influence of quality on the decision to visit, it was found that it has a contributing influence on the decision of tourists to visit Je'ne Tallasa Sileo Baths, Gowa Regency. The influence of facilities on the decision to visit was found to have a significant contribution to the decision of tourists to visit Je'ne Tallasa Sileo Baths, Gowa Regency. The influence of location on the decision to visit was found to have a significant contribution to the decision of tourists to visit the Je'ne Tallasa Sileo Baths, Gowa Regency. The influence of quality, facilities and location on the decision to visit was found to have a significant simultaneous contribution to the decision of tourists to visit Je'ne Tallasa Sileo Baths, Gowa Regency.